Engaging Buddhism why it matters to philosophy - Garfield, Jay L. 1955- (Oxford University Press, 2015)
Articulating the basic metaphysical framework common to Buddhist traditions, this book explores questions in metaphysics, the philosophy of mind, phenomenology, epistemology, the philosophy of language, and ethics as they are addressed in a variety of Asian Buddhist traditions. Focusing on philosophical problems, in each case the connections between Buddhist and contemporary Western debates are examined, as are the distinctive contributions the Buddhist tradition can make to Western discussions